DNA damage and repair assessed by comet assay in workers exposed to lead in a battery recycling. - Mahara Valverde; María Maldonado; Efraín Tovar (Frontiers in Genetics, 2015)
Occupational exposure to xenobiotic mixtures is an actual concern to public health effects. The automobile battery recycling industry, contribute to lead and cadmium exposure as a mixture for worker in several countries (Palus et al., 2005). In the last decade, the use of comet assay in human biomonitoring has been a successful tool (Valverde and Rojas, 2009), that we apply for this three year follow-up biomonitoring study in a group of recycling battery workers in Guanajuato, Mexico (n=85) in terms of determine early biomarkers. Exposure and effect biomarkers of molecular epidemiology were determined, lead whole blood levels and ALA-D activity as exposure biomarkers meanwhile, DNA damage, DNA repair, and oxidative stress as effect biomarkers. Our results indicate that battery-recycling workers are exposed to high levels of lead in whole blood (56.95 ± 2.7 g/dL), almost five times higher to the permissive level (10 g/dL). Also, inhibition of ALA-D enzyme activity (164 ± 0.04 nmoles/h/ml) was significant, with respect to control group (704.23 ± 8.3 nmolas/h/ml). At respect to effect biomarkers, we determine high levels of oxidative stress analyzed by TBARS technique (1.31 MDA nmolas/ml) with respect to the control group (1.05 MDA nmolas/ml). The basal DNA damage found in the exposed group was about 47% higher than control group, meanwhile their DNA repair activity decreased in about 28% relative to control group. These findings may suggest that lead exposure into the battery recycling environment is a fact that exceeds the permissive lead exposure levels, reflected also in the inhibition of an important enzyme involved in hemo biosynthesis, ALA-D. The mechanism of toxicity involves generation of oxidative stress that affects lipids and DNA. DNA damage determined as single strand breaks, is not repaired efficiently, indicating low base excision repair capacity that may have a variety of health effects. In addition to these findings, DNA damage determined by comet assay was sensible to reflect lead exposure levels related to specific activities inside this factory. Human biomonitoring studies through comet assay could be robust when additional biomarkers are determined at time.